CORONECTOMY AS A METHOD FOR SURGICAL TREATMENT OF IMPACTED MANDIBULAR THIRD MOLARS: INDICATIONS AND OWN CLINICAL STUDIES OF POSTOPERTIVE PERIOD - Tkachenko, P.I.; Hohol, A.M.; Pankevych, A.I.; Kolisnyk, I.A.; Dobroskok, V.O. (World of Medicine and Biology, 2019)
Retrospective analysis of archival material and results of clinical surveillance of patients with dystopy and retention of the mandibular third molars, starting from the pre-operative examination, the content of operation protocols, identification of the nature of the clinical course in the postoperative period and determination of the volume of rehabilitation activities is crucial in the choice of optimal terms and options for operative intervention and their medication management in this category of patients. The paper was aimed at summarizing of the main radiological signs to the indication for coronectomy of the mandibular third molars considering the anatomical position of the teeth, possible complications, and determination of the terms of roots extraction after coronectomy. Generally, during the period of study of dystopy and retention of the mandibular third molars, 32 surgeries were conducted using the method of coronectomy. Findings of the retrospective analysis of archival material showed that in 64.63% of cases absence of sufficient space for mandibular third molars eruption was observed, which confirms the involution theory of teething delays. In all cases the crown part of the tooth was covered with mucous membrane, and in 75% of cases it was partially or completely covered with osseous tissue. The greatest complexity of coronectomy of the mandibular third molars and the probability of occurrence of sensory disturbances is specific for the position of the C2-C3 teeth according to G. Pell, B. Gregory (1933) classification. The analysis of existing clinical material provides grounds for determination of basic radiological indications for application of this method of operative intervention: 1. Significant distortion, narrowing, doubling with the formation of longitudinal groove and growing of X-ray permeability of the apical third of the roots of the mandibular third molars near the mandibular canal. 2. Noncontinuous contours, deviation or narrowing of the mandibular canal in close proximity to mandibular third molars. During the period of study, in the postoperative period 2 patients (6.25%) presented with sensory disturbances in the zone of the innervations of the lower alveolar and lingual nerves. In the postoperative period 7 patients (21.88%) presented with the phenomena of traumatic pulpitis, though this did not require any additional surgery and pain syndrome spontaneously disappear within 2-3 days under the effect of non-steroidal anti-inflammatory drugs (ketorolac, nimesulid). In the observation group, the arithmetical mean value of the range of roots migration from the site of the pre-operative location was 3.6 ± 1,69 mm within 12 months of postoperative intervention, therefore, the most optimal term of repeated surgery aimed at roots extraction should be the interval from 12 to 24 months following the coronectomy. Clinical surveillance of patients after coronectomy of the mandibular third molars is necessary for further clarification of mechanisms of readjustment of bone structures and factors, influencing on this process in postoperative period.